Pengaruh Waktu Pemangkasan Dan Dosis Pupuk Kalium Terhadap Hasil Tanaman Mentimun (Cucumis sativus L.) - Suprapto (Indoensia), Agus; Iftitah (Indoensia), Siti Nurul; Safitri (Indoensia), Desi (JURNAL VIGOR, 2023)
Cucumber (Cucumis sativus L.) is type of fruit vegetable that is widely consumed by the people of Indonesia. Cucumber cultivation is still not intensive, that is many farmers do not do pruning and use inappropriate doses of fertilizers, so it is necessary to improve cultivation techniques through proper pruning and fertilization. This purpose of this study is to determine the effect of pruning time and dose of potassium fertilizers on cucumber crop yields. The research was carried out from January 9 to March 18, 2022 in Ngencek, Kalikuto, Grabag, Magelang, with an altitude of 510 m asl. The method of the research was factorial arranged in a completely randomized complete block design (RCBD) with two factors. The first factor is pruning time of 21 hst and 28 hst. The second factor is the dose of potassium fertilizers consisting of 0 kg/ha, 80 kg/ha, 160 kg/ha, and 240 kg/ha. The results showed that the pruning time of 21 days after planting had a significant effect on the flowering age of cucumber plants. Different doses of potassium fertilizers had no effect on plant length, flowering age, number of fruit per plant, weight per fruit, fruit weight per plant, fruit length, fruit diameter, and fruit volume. There was no interaction between pruning time and the dose of potassium fertilizers given.Keywords: Cucumis sativus L., doses, potassium fertilizers, pruning time.